Rainwater as an alternative to saving urban clean water which has economic value: Interaction human and conservation - Gulo, Edison Reinkarnasi; Mustafa, Annisa Fitri (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: Rainwater Harvesting System (RHS) is an alternative solution that can overcome the problem of demand of urban water with high population density and as a prevention of potential flooding due to lack of catchment areas. Central Jakarta's high population density triggers a large demand for clean water, causing excessive groundwater exploitation and a long impact on groundwater scarcity and seawater intrusion. The implementation of RHS in Indonesia is still relatively rare, especially in Jakarta. Therefore, the purpose of this research is to planning RHS design as an alternative to meet the urban water demands. This research innovates on RHS designs based on water demands and aspects of the feasibility in economics.  Methods: This research was conducted quantitatively and data collection was carried out by mix method, the number of occupants data was collected through observation and literature review of previous RHS research. The analysis of RHS is carried out mathematics and descriptive. Findings: The result showed that the implementation of RHS at X Boarding House succeeded in saving clean water bills by up to 58% with benefit value of IDR 8,093,176. This shows that the RHS is an effective solution in reducing water costs for PDAM bills. The design of the RHS uses roof as catchment area and the tank system is placed above ground taking into ease of operation and maintenance. Benefit Cost Ratio (BCR) analysis shows that the RHS at X Boarding House is feasible to be built with a value of 1,388>1 which shows that the value of the benefits exceeds the  costs. Conclusion The importance of using rainwater as an alternative to saving clean water by economic value shows that RHS can be an alternative solution to overcome problems, especially water availability during the dry season when the supply of clean water is decreasing. Novelty/Originality of this article: This research makes a novel contribution by presenting an RHS design tailored to urban water demand and its economic feasibility, as well as considering operational aspects under Jakarta's unique climatic and environmental conditions.